(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
This essay examines Karl R. Popper’s philosophical and epistemological thesis in an attempt to analyze it and consider its applicability as a cognitive instrument in the field of creativity. It also reviews the philosophical basis that underpins its frame of reference for approaching reality; as well as its framework, and limits on the epistemological level. Popper’s methodological proposal is reviewed, and the correspondence that he posits between science and art. His epistemological categories are linked to the field of creativity, while exploring their scope as instruments for demonstrating and projecting validity.